Factors Influencing Post-traumatic Growth in Mothers with Premature Infants Admitted to the Neonatal Intensive Care Unit - Hyeun Soo Lee; Sook Jung Kang (Child Health Nursing Research, 2020)
Purpose Caring for a vulnerable premature baby is a challenging task, but some mothers experience growth through that process. The purpose of this study was to investigate the factors influencing post-traumatic growth in mothers with premature infants admitted to the neonatal intensive care unit. Methods A correlational research design was used and 105 mothers of premature infants were recruited from an online community. Data were collected from January 15 to January 25, 2019. Post-traumatic growth was measured using the Korean version of the Posttraumatic Growth Inventory. Data were analyzed using descriptive statistics, the t-test, analysis of variance, the Scheffé test, Pearson correlation coefficients, and hierarchical multiple regression. Results The final model developed in this study explained 45.5% of post-traumatic growth (F=13.66, p<.001). Resilience (β=.54, p<.001) was the strongest predictor of post-traumatic growth, followed by the age of the mother when giving birth (β=.17, p=.028) and current employment status (β=.17, p=.049). Conclusion For mother with premature infants to grow psychologically after their experience, it may be needed to support them to develop and strengthen their resilience through either education or their own support network.